Analisis Calendar Anomalied di IHSG dalam Perioda Sebelum dan Selama Krisis Global (Januari 2004-Desember 2011) - , Risyanto Krisna Suryaputra ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aims to analyze the phenomenon of calendar anomalies consisting of the January effect, weekend effect and the turn-of-the-month effect occurs in the IHSG in Indonesia Stock Exchange before and during the global crisis. This study utilize using a t-test (one-sample t-test) and multiple regression test with dummy variables. The results showed that January and Weekend effect does not occur in the IHSG in period before and during the global crisis, while testing turn-of-the-month Effect occurred before the global crisis, but the period during the global crisis phenomena turn-of-the-month effect does not occur.